Popular Music in Southeast Asia : Banal Beats, Muted Histories - Keppy, Peter (Amsterdam University Press, 2017)
From the 1920s on, popular music in Southeast Asia was a mass-audience phenomenon that drew new connections between indigenous musical styles and contemporary genres from elsewhere to create new, hybrid forms. This book presents a cultural history of modern Southeast Asia from the vantage point of popular music, considering not just singers and musicians but their fans as well, showing how the music was intrinsically bound up with modern life and the societal changes that came with it. Reaching new audiences across national borders, popular music of the period helped push social change, and at times served as a medium for expressions of social or political discontent.